The Performance of Bachelor's Degree Management Program Lecturers at Purwasukasi Private University: The Role of Self-Efficacy, Knowledge Sharing, and Lecturer Engagement. - Suherman, Enjang; Sudirman, Iman; Juniarti, Atty Tri (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The aim of this research is to analyze self-efficacy and share knowledge regarding lecturer involvement, which has implications for lecturer performance. This research method is descriptive verification by analyzing the direct and indirect influence of the independent variable on the dependent variable and can describe the condition of each variable. The sample used was 216 from a population of 326 permanent lecturers in the undergraduate management study program (Isaac & Michael's table technique). Data collection through interviews and questionnaires with descriptive statistical analysis and path analysis. The results of descriptive research show that self-efficacy in conditions is quite strong with the dimensions of magnitude, strength and generality. Knowledge sharing conditions are rare with the dimensions of Knowledge Donate and Knowledge Collecting. Meanwhile, lecturer involvement is quite strong with the dimensions of Dedication, Vigor and Absorption. And the performance of lecturers is in the quite good category with the dimensions of the tridharma of higher education. The results of verification research show that self-efficacy and knowledge sharing have a partial and simultaneous positive effect on lecturer involvement, and lecturer involvement has a positive and significant effect on lecturer performance. In this way, lecturer performance can be improved through